Housing Markets and the Economy: The Assessment. - Muellbauer, J; Murphy, A (2008)
Housing markets have multiple interactions with the rest of the economy and these are surveyed in this paper. The drivers of house prices include income, the housing stock, demography, credit availability, interest rates, and lagged appreciation, the latter a potential mechanism for overshooting. There is rather less agreement on the determinants of new construction, though planning constraints are widely seen as a major issue and one of the causes of the UK housing affordability problem. The paper argues that housing collateral and downpayment constraints are the key to understanding the role of house-price variations in explaining medium-term consumption fluctuations. Institutional variations between countries and over time account for major differences in linkages between house prices and economic activity. This illuminates debates about how monetary and other policy should react to house-price variations. The paper also discusses the role of housing markets in explaining regional migration and location decisions, intergenerational inequality, and restricting access of the less affluent to public goods, such as good schools, which are capitalized in local house prices.